ANTIOXIDANT ACTIVITIES OF SOME LESS UTILIZED EDIBLE FRUITS - Dasgupta, Sumita; Pandya, Maitry; Patel, Nirali (International Journal of Current Pharmaceutical Research, 2017)
Objective: The objective of the present study was to evaluate the total phenolic (TPC) and flavonoid content (TFC) of five less utilized fruits such as Aegle marmelos, Spondias pinnata, Limonia acidissima, Averhoa carambola, Crescentia cujete and was compared with Phyllanthus emblica, (Amla) well known for its antioxidant activities. Total phenolic and flavonoid contents of samples were correlated with antioxidant activities like 1,1-Diphenyl-2-Picryl-Hydrazyl (DPPH) free radical scavenging assay, Ferric reducing antioxidant potential (FRAP) assay and total antioxidant capacity (TAC). Methods: The total phenolic of each fruit extract were determined by the Folin-Ciocalteu method with some modifications and the total flavonoids were estimated by Aluminum trichloride colourimetric method. The DPPH antioxidant assay, The FRAP assay and TAC were determined spectrophotometrically. Results: The total phenolics were expressed as mg/100g Gallic acid equivalent (mg GAE/100 gm) and the total flavonoids were expressed as mg/100g Quercetin equivalent (mg QE/100 gm). TPC was found to be maximum in Spondias pinnata with 142.16 mg GAE/100 gm where as TFC was maximum in Phyllanthus emblica with 91.1 mgQE/100 gm. DPPH radical scavenging activity was expressed n percentage(%),Â FRAP values expressed as mg/100g Ascorbic equivalent (AAE) and the total antioxidant activity was expressed as mg/100g Ascorbic equivalent. Maximum DPPH radical scavenging activity was shown by Spondias pinnata (93.75%), FRAP values were maximum in Phyllanthus emblica with 72.6 mg AAE/100 gm and total antioxidant capacity was found to be highest in Spondias pinnata (50.1 mg AAE/100 gm). Conclusion: Spondias pinnata, an underutilized fruit, was found to be promising with antioxidant activities comparable to Phyllanthus emblica.